The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12860-021-00348-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of MUSASHI1 in epithelial breast cancer cells is due to down regulation of miR-125b

Abstract: Background Musashi1 (MSI1) is an oncogenic protein with a crucial role in the proliferation and characteristics of the epithelial cells in breast cancer. The change in expression of MSI1 has a role in solid tumor progression. There are different factors that regulate MSI1 expression in various cancer tissues including microRNAs which are considered as one of the most important of these factors. The aim of our study is identification of the molecular cause of maximal expression of MSI1 in epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…MSI-1 was co-localized with E-cadherin, a key epithelial marker, in immunohistochemistry measurements. Finally, MSI-1 and MSI-2 were higher expressed in predominantly luminal breast cancer cell lines compared to basal cells, a finding reproduced by another group [ 65 ]. Katz et al also found that MSI-1 overexpression decreased migration and MSI-2 overexpression reduced ductal branching [ 60 ].…”
Section: Musashi Proteins In Female Malignanciessupporting
confidence: 74%
See 1 more Smart Citation
“…MSI-1 was co-localized with E-cadherin, a key epithelial marker, in immunohistochemistry measurements. Finally, MSI-1 and MSI-2 were higher expressed in predominantly luminal breast cancer cell lines compared to basal cells, a finding reproduced by another group [ 65 ]. Katz et al also found that MSI-1 overexpression decreased migration and MSI-2 overexpression reduced ductal branching [ 60 ].…”
Section: Musashi Proteins In Female Malignanciessupporting
confidence: 74%
“…Using methylation analyses in primary breast cancer specimens, Kagara and colleagues found that MSI-1 promotor methylation (which was inversely correlated with gene expression) was lowest in TNBC, similar to other stem cell markers, including CD44 and CD133 [ 62 64 ]. Finally, Forouzanfar and colleagues demonstrated that MSI-1 expression depends on miR-125b in breast cancer [ 65 ].…”
Section: Musashi Proteins In Female Malignanciesmentioning
confidence: 99%
“…Among them, the expression level of miR-637 in various cancer tissues was significantly lower than that in adjacent tissues, including glioblastoma and lowgrade gliomas (GBM/LGG) [8][9][10][11], papillary thyroid carcinoma (PTC) [12,13], non-small cell lung cancer (NSCLC) [14], gastric cancer (GC) [15][16][17], hepatocellular carcinoma (HCC) [18][19][20][21], CRC [22], pancreatic ductal adenocarcinoma (PDAC) [23], human cholangiocarcinoma (CHOL) [24], oral squamous cell carcinoma (OSCC) [25], prostate cancer (PCa) [26], ovarian cancer (OC) [27,28], triple-negative breast cancer (TNBC) [29], cervical cancer (CCa) [30], osteosarcoma (SaOS) [31,32], multiple myeloma (MM) [33], chronic myeloid leukemia (CML) [34]. In addition, the expression level of miR-637 was lower in the cell lines of various cancer cells than the corresponding normal cell lines, including PTC [12,13], GC [17], HCC [18,21], OSCC [35], PDAC [23], CHOL [36], TNBC [37], breast cancer (BRCA) [38], SaOS [31], etc. In the serum of CHOL patients, the expression level of miR-637 was lower than that of healthy people [39].…”
Section: Mir-637 Is Abnormally Expressed In Human Cancersmentioning
confidence: 99%